A low-cost ball and plate system for advanced control education. Issue 4 (October 2015) - Parga, Carlos; Yu, Wen; Li, Xiaoou
This paper describes a ball and plate system for graduate education. We explain how to use this system for nonlinear system modeling, and how to use advanced control techniques for this interesting and impressive equipment. The main contribution of the paper is this ball and plate system which is of low cost compared with the other commercial education equipments. Several open problems in areas of electrical engineering and control are discussed. The paper also presents some initial ideas to create a low-cost laboratory platform.